Neotype designation for Cladotanytarsus (Lenziella) bicornutus (Kieffer), and first description of the distinctive female (Diptera: Chironomidae: Tanytarsini) - Giłka, Wojciech; Spies, Martin (Zootaxa, 2012)
A neotype for Cladotanytarsus (Lenziella) bicornutus (Kieffer, 1922), the type species of Lenziella Kieffer, 1922, is designated from material sampled by Krüger in the 1940’s and recently discovered in the Thienemann collection. The adult female of C. (L.) bicornutus is described for the first time, and its diagnostic characters are discussed.